Disasters and Climate Change: A Paradigm Shift - Amaly Fong Lee; Adán Vega Sáenz (Revista de Estudios Latinoamericanos sobre Reducción del Riesgo de Desastres, 2023)
It is very common to directly associate climate change with disasters; however, the reality is that the relationship between these is complex, without necessarily implying a cause-effect relationship. From the side of disaster risk management, an evolution associated with climate change is established, with which some ambiguities, confusions and incorrect use of terms have arisen, which has caused some concepts to become distorted and generate confusion. On the other hand, today it is common to hear inappropriate terms that continue to be part of the vocabulary of society in general and even of decision makers. The foregoing causes that the true meaning of two disciplines of vital importance for society, continue to be distorted, such as: disaster risk management and climate change. Due to this, the measures adopted are equally scattered, isolated, and poorly coordinated. In this article, we present a broad view of the scientific scope, with universally recognized knowledge of both disciplines, emphasizing the historical evolution of both, mainly seeking a normalization of knowledge and an orderly conceptualization of the most important aspects of risk management of disaster.